PENINGKATAN PRESTASI BELAJAR SISWA SLB NEGERI KOTA LANGSA MELALUI APLIKASI SELF PRO - Desi Sinamo, Yemima; Evanita Lubis, Dian; Chairiyah Jambak, Maulidina; Ayu Lestari, Putri; Arico, Zulfan (Jurnal Masyarakat Berdikari dan Berkarya (Mardika), 2024)
Langsa City State Special School (SLB) is one of the SLBs in Langsa City. Langsa State SLB has a total of 244 students, with 64 people with physical disabilities, 34 people with visual impairments, 53 people with hearing impairments, 64 people with mental disorders and 29 people with mental physical disorders. Langsa City State Special School has a problem, namely the lack of student interest in learning activities, in 2023 students tend to feel bored and not focused in the process of receiving knowledge from teachers. Based on the needs assessment from the results of interviews with teachers, an understanding of the importance of understanding digitalization technology in the learning process is needed, especially through mentoring who knows the concepts and development of children with special needs. Based on 10 indicators of achievement of output targets, PKM-PM activities have reached 99%. Activities that have not been fully achieved are the final report which is still 10% in progress. From the results of the PKM-PM activity entitled "SELF PRO: Self Improvement Application for Langsa SLB Students in Improving Learning Achievement", there was an increase in results which had an impact on the education of students and teachers. These results can be seen from the students' pre-test and post-test scores. The great value of understanding the Self Pro application is because using the application is very easy and does not require an internet connection.